UV curing ink-jet printing power battery blue film ink and UV curing coating
By adjusting the proportion of the components in the blue film ink in the blue film ink ink inkjet in ink, the problem of the power battery blue film in the existing technology is too much viscosity at high temperature conditions, and realizes the high viscosity and low viscosity at high viscosity at room temperature at room temperature. Taking into account both to ensure the fluency of inkjet printing and the insulation performance of coating.
Patent Information
- Application Number
- CN202411349626.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, the insulation performance and other protective properties of the power battery blue film cannot meet the industry needs of new energy vehicles, especially under high temperature conditions, the viscosity of traditional insulating paint is too high and is not suitable for inkjet printing processes, and it cannot be Achieve uniform coating at edges and corners.
Provides a UV curing inkjet printing power battery blue film ink. By adjusting the mass ratio of acrylic resin and UV photocurable monomer, and adding hydrophobic monomers, additives and photoinitiators, the ink ensures high performance at room temperature. The viscosity is reduced when spraying under high temperature conditions, thereby solving the smoothness problem of inkjet printing.
Maintain high viscosity at room temperature to meet the inkjet printing needs, and decreases viscosity when spraying under high temperature conditions, ensuring smooth spraying, solving the problem of printing edges at the corners, and improving the insulation and protective performance of the coating.
Smart Images

Figure CN119350922A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of UV curing polymer materials and relates to a UV curing inkjet printing power battery blue film ink and a UV curing coating. Background Art
[0002] In recent years, with the increasing environmental pollution, the new energy industry has attracted more and more attention. As an important component of electric vehicles, lithium-ion power batteries have a direct impact on the promotion and use of electric vehicles due to their safety performance, energy density and cycle life, and have therefore attracted widespread attention. At present, the last step in the preparation of lithium-ion power batteries in new energy vehicles is to wrap the battery with a layer of blue protective film (referred to as "blue film"). As an insulating material, the blue film can be widely used on the surface of power battery modules to achieve isolation between battery cells and prevent the failure of a single battery cell from affecting other battery cells. In addition, the blue film also has waterproof and dustproof functions, which can better protect the battery.
[0003] However, the insulation and other protective properties of traditional battery blue films can no longer meet the current industry needs of power vehicles: for example, scratches, breakages, and wrinkles are prone to occur during the production process, and these defects not only affect the appearance of the product, but may also damage the product function; and the uneven thickness, poor adhesive properties, impact resistance, wear resistance, corrosion resistance, acid and alkali resistance, aging resistance and other problems of traditional battery blue films further limit their application. Therefore, it has gradually been replaced by a new UV insulation coating solution. In the prior art, the coating is prepared by inkjet printing to ensure that the coating thickness is highly uniform and the deviation is small, which is suitable for the production of blue film insulation coatings. However, under relatively high temperature conditions (greater than 60°C), the viscosity of the insulating varnish used in other existing processing methods (spraying, printing, etc.) is much higher than 40mPa·s, which is not suitable for inkjet printing technology.
[0004] In this regard, the existing Chinese patent document (publication number CN116445036A, publication date July 18, 2023) discloses a UV curable inkjet printing insulating ink. Although the ink has low viscosity and is very suitable for inkjet printing process, the viscosity of the ink is too low, and the viscosity is only about 10cps at 45°C. It is only suitable for printing and patterning on the surface of a flat substrate, and cannot achieve uniform coating at the corners of the power battery housing, thereby failing to solve the problem of printing hemming at the corners. In addition, the ink cannot maintain high viscosity at room temperature to meet the requirements of inkjet printing, and a lower viscosity is required when the nozzle is sprayed to ensure smooth spraying.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a UV-curing inkjet printing power battery blue film ink and a UV-curing coating. The ink can achieve a high viscosity at room temperature (25°C) and a low viscosity when the ink is sprayed from the nozzle under a high temperature (60-95°C) environment, thereby solving the technical problem that the existing insulating paint has high viscosity and is not suitable for inkjet printing. The viscosity of the ink increases rapidly after being sprayed, which can solve the problem of printing hemming at the corners of the power battery casing.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] In a first aspect, the present invention provides a UV-curable inkjet printing power battery blue film ink, comprising the following components in parts by mass: 25 to 80 parts of an acrylate resin, 15 to 40 parts of a UV photocurable monomer, 2 to 10 parts of a hydrophobic monomer, 0.1 to 1 part of an auxiliary agent, 2 to 8 parts of a photoinitiator and 2 to 7 parts of a color paste; wherein the mass ratio of the acrylate resin to the UV photocurable monomer is 1:(1.5 to 3).
[0009] Preferably, the ink comprises the following components in parts by weight: 25 to 70 parts of an acrylic resin, 20 to 35 parts of a UV photocurable monomer, 2 to 6 parts of a hydrophobic monomer, 0.1 to 1 part of an auxiliary agent, 2 to 8 parts of a photoinitiator and 2 to 7 parts of a color paste.
[0010] Furthermore, the acrylic resin is one or a mixture of polyurethane acrylate or acrylated polyacrylate;
[0011] The polyurethane acrylate is any one of difunctional or higher-functional polyurethane acrylate and aliphatic polyurethane acrylate, and the viscosity of the polyurethane acrylate is 10 to 8000 cps at 25° C. and 600 to 5000 cps at 60° C.
[0012] Among them, the difunctional or higher polyurethane acrylates are R7162 of Guangzhou Runao Chemical Materials Co., Ltd. (hereinafter referred to as Runao Chemical), FSP7405 of Runao Chemical, DR-U021 of Changxing Chemical Industry (China) Co., Ltd. (hereinafter referred to as Changxing Chemical), Sartomer 33118 or B-270 of Guangdong Boxing New Materials Technology Co., Ltd. (hereinafter referred to as Boxing New Materials);
[0013] The aliphatic polyurethane acrylate is ETERCURE 61280 of Changxing Chemical, ETERCURE 6153-3 of Changxing Chemical, 6115T-80 of Changxing Chemical, and hexafunctional aliphatic polyurethane acrylate PUA2630D of Nanxiong Sanben Chemical Technology Co., Ltd.
[0014] Furthermore, the acrylic acid esterified polyacrylate has a viscosity of 3000-40000 cps and a glass transition temperature (Tg temperature) of 50-100°C at room temperature (25°C).
[0015] Among them, the acrylated polyacrylates are the difunctional 4312IH of Tianjin Boruncheng Technology Co., Ltd. (referred to as Tianjin Boruncheng), ETERCURE 6530B-40 of Changxing Chemical, and ETERCURE 6533B-40 of Changxing Chemical.
[0016] Preferably, the polyurethane acrylate has a viscosity of 1000 to 7000 cps at room temperature (25° C.) and a viscosity of 800 to 4500 cps at 60° C.;
[0017] The viscosity of acrylic acid ester polyacrylate is 3000-35000cps at 25℃, and the Tg temperature is 60℃-90℃. The selection of acrylic acid ester polyacrylate with Tg temperature in this range can generally increase the Tg temperature of UV curing inkjet printing power battery blue film ink, thereby weakening the elasticity of the molecular chain and improving the overall boiling resistance of the ink (because too low Tg will lead to a decrease in boiling resistance).
[0018] Furthermore, the UV photocurable monomer is a mixture of a monofunctional UV photocurable monomer and a difunctional UV photocurable monomer, and the mass ratio of the monofunctional UV photocurable monomer to the difunctional UV photocurable monomer is (0.3-1.5):1.
[0019] Preferably, the monofunctional UV photocurable monomer is an aliphatic or alicyclic (meth)acrylic acid photocurable monomer; for example, it can be any one of isobornyl acrylate, hydroxyethyl (meth)acrylate, dicyclopentadiene (meth)acrylate, isobornyl methacrylate or 2-ethylhexyl methacrylate.
[0020] Preferably, the bifunctional UV photocurable monomer includes any two or three of dipropylene glycol diacrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, tricyclodecane dimethanol diacrylate, ethoxylated 1,6-hexanediol diacrylate, 1,4-butanediol diacrylate, propoxylated neopentyl glycol diacrylate, 2-methyl-1,3-propanediol diacrylate, 3-methyl-1,5-pentanediol diacrylate, ethylene glycol dimethacrylate, tripropylene glycol dimethacrylate, triethylene glycol dimethacrylate, diethylene glycol dimethacrylate or tricyclodecane dimethanol dimethacrylate.
[0021] It should be noted that in order to obtain a UV-curable inkjet printing power battery blue film ink having a high viscosity of 100 to 120 cps at room temperature (25°C) and a viscosity of only 20 to 30 cps during nozzle printing (high temperature environment, 60 to 95°C), the present invention adopts the following overall formula: the mass ratio of acrylic resin to UV photocurable monomer is 1:(1.5 to 3); at the same time, the mass ratio of monofunctional UV photocurable monomer to difunctional UV photocurable monomer is (0.3 to 1.5): 1. This effect can only be achieved when the ratio is controlled within the above range.
[0022] Preferably, the bifunctional UV photocurable monomer is selected from any two of dipropylene glycol diacrylate (DPGDA), tripropylene glycol diacrylate (TPGDA), 1,6-hexanediol diacrylate (HDDA), tricyclodecane dimethanol diacrylate (DCPDA), for the following reasons:
[0023] Since tripropylene glycol diacrylate (TPGDA) and dipropylene glycol diacrylate (DPGDA) can increase the curing speed of the coating, these two monomers have a faster reaction speed and can accelerate the curing process of acrylic resins and UV photocurable monomers, so that the ink can be quickly cured after being sprayed by the nozzle, thereby meeting the requirement of uniform edge wrapping of the battery shell during printing; at the same time, the addition of TPGDA or DPGDA can also improve the flexibility of the coating, because these two monomers can undergo cross-linking reaction with acrylic resins during the curing process to form an elastic cross-linking structure, so that the coating after the ink is cured has good flexibility, can adapt to the deformation and vibration of the power battery shell, and can also improve the dilution power of the ink on the color paste.
[0024] Since tricyclodecane dimethanol diacrylate (DCPDA) can improve the weather resistance of the coating, and the viscosity of tricyclodecane dimethanol diacrylate (DCPDA) at room temperature (25°C) is 110-150cps, which is higher than the viscosity of other photocurable monomers (<50cps), the viscosity value of the overall system can be adjusted to a suitable range. At the same time, due to the presence of dihydroxyl functional groups, the corresponding acrylate has the advantages of high Tg temperature, good adhesion, aging resistance, good wear resistance, low shrinkage and fast curing speed, etc., and can be used together with monofunctional UV photocurable monomers, tripropylene glycol diacrylate (TPGDA) or dipropylene glycol diacrylate (DPGDA) to provide more crosslinking points for the ink coating and improve the curing speed.
[0025] That is to say, the present invention can achieve a good balance between curing speed, ink viscosity, crosslinking density, improved film strength and flexibility, weather resistance and thermal stability through the compounding of active functional monomers with different functionalities; by enhancing the adhesion of the photocurable inkjet ink film, the inkjet efficiency is improved. The above monomers have a good swelling effect on the metal substrate, can penetrate into the shallow surface layer of the substrate, and form an interpenetrating network structure after curing. For example, the two acrylic groups in tricyclodecane dimethanol diacrylate (DCPDA) can react with another monomer containing multiple double bonds to form a crosslinking point, which can effectively improve the mechanical properties, thermal stability and other physical and chemical properties of the photocurable coating. The formation of an interpenetrating network structure can accelerate the curing process because the network structure provides more reaction sites, making the reaction between the monomer and the initiator more rapid and uniform. Similarly, when the ink is heated to 60°C during nozzle spraying, the above monomers are used in combination with monofunctional monomers to generate a stable interlayer interpenetrating network structure, which significantly improves the adhesion of the coating. In addition, 1,6-hexanediol diacrylate (HDDA) can increase the crosslinking degree of the coating, thereby improving the weather resistance of the coating.
[0026] It should be noted that the interpenetrating network structure formed by the present invention depends on the specific polymerization conditions, the selection of initiators and crosslinking agents, and the compatibility between polymers. The present invention sets the mass ratio of monofunctional UV photocurable monomers to bifunctional UV photocurable monomers to (0.3-1.5):1, and uses appropriate initiators and crosslinking agents to synthesize materials with interpenetrating network structures, which not only helps to improve the mechanical strength and chemical resistance of the material, but also improves its flexibility, because the network structure provides more physical barriers, reduces the slippage inside the material, and thus enhances the overall performance of the material.
[0027] Furthermore, the hydrophobic monomer is an acrylic acid ester hydrophobic monomer having an ester group carbon chain length of C8 to C18, specifically any one of lauryl acrylate (LA), octyl acrylate, decyl acrylate, tetradecyl acrylate (TDA), hexadecyl acrylate (HDA), octadecyl acrylate, undecyl methacrylate, lauryl methacrylate, tetradecyl methacrylate, and octadecyl methacrylate, or a combination of two or more thereof.
[0028] In the present invention, the hydrophobic monomer and the UV photocurable monomer are used in combination, and the hydrophobic modification increases the degree of crosslinking between molecules, makes it easier to form a molecular network structure, and increases the degree of crosslinking between polymer molecules, thereby improving the flexibility and curing speed of the coating.
[0029] Furthermore, the auxiliary agent includes a surfactant and a free radical polymerization inhibitor; wherein the surfactant may be BYK3575, BYK333 or other surfactants; the free radical polymerization inhibitor may be selected from at least one of 2,6-di-tert-butyl-p-cresol, N-nitroso-N-phenylhydroxylamine aluminum, triphenylphosphine, p-methoxyphenol, and hydroquinone, and the purpose of adding the inhibitor is to improve the stability of the resin composition during storage and inhibit unintentional free radical polymerization reactions.
[0030] Preferably, the added mass ratio of surfactant and free radical polymerization inhibitor is 1: (1-2). In order to adapt to 60°C nozzle printing, high temperature sites above 90°C may appear in the local area of the equipment during overall heating. Therefore, the ink is required to have good thermal stability at 100°C for a certain period of time, otherwise it will cause blockage of the printing nozzle. By controlling the added mass ratio of surfactant and free radical polymerization inhibitor, the thermal stability of the original slurry is improved to assist high-viscosity printing.
[0031] Further, the photoinitiator is a mixture of any one or more of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (trade name 819), 2-isopropylthioxanthone (ITX), 1-hydroxycyclohexylphenyl ketone (trade name 184), benzophenone (BP), bis-2,6-difluoro-3-pyrrolophenyl titanocene (trade name 784), and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (TPO), 2,4-bis(trichloromethyl)-6-methyl-1,3,5-triazine, 4,4'-bis(dimethylamino)benzophenone, 4,4'-dichlorobenzophenone, 3,3'-dimethyl-2-methoxybenzophenone, and hydroxybenzophenone.
[0032] Furthermore, the color paste includes tetrahydrofuran acrylate, color powder and a dispersant.
[0033] In the present invention, the preparation method of the color paste is: tetrahydrofuran acrylate, color powder and dispersant are mixed, and ground to the following sizes: D50 particle size is 50-105nm, and D99 particle size is less than 300nm.
[0034] Preferably, the color paste is phthalocyanine blue paste, and the preparation method of phthalocyanine blue paste includes: mixing 100 parts of a total mass, including 30 parts of phthalocyanine blue BGS color powder, 4 parts of DisperBYK-2117 dispersant and 66 parts of THFA monomer, and grinding them to the following sizes: D50 particle size is 50-105nm, and D99 is less than 300nm.
[0035] In the second aspect, the present invention discloses a UV-curable coating, which is made by inkjet printing of some or all of the above-mentioned UV-curable inkjet-printed power battery blue film ink. Among them, the thickness of the existing UV-curable coating generally does not exceed 70μm, but the present invention requires a one-time film thickness of 100-120μm. The present invention introduces the above-mentioned photoinitiator, which is highly compatible with the polymer and is conducive to forming an interpenetrating network structure, thereby improving the curing rate of the coating and ultimately achieving one-time coating.
[0036] In a third aspect, the present invention also provides a method for preparing the above-mentioned UV curing coating, and the specific preparation process is as follows:
[0037] Step 1: attach the above-mentioned UV curable inkjet printing power battery blue film ink to the surface of the power battery shell by inkjet printing, and the specific printing nozzle can be XAAR nozzle;
[0038] Step 2: pre-curing the surface after inkjet printing in step 1 by using a UV-LED lamp, and then inkjet printing again on the pre-cured surface, repeating the above pre-curing step twice, and finally inkjet printing again on the pre-cured surface, and then using a UV-LED lamp for UV curing;
[0039] Step 3: Use an electrodeless lamp to perform electrodeless lamp curing on the surface after UV curing in step 2, and finally form a cured coating.
[0040] In addition, the present invention also provides an application of UV curing inkjet printing power battery blue film ink in the preparation of an organic barrier film for a power battery shell.
[0041] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0042] 1) The UV curable inkjet printing power battery blue film ink provided by the present invention can spray the ink material under relatively high temperature (60-95°C) conditions when using a dedicated inkjet print head for spraying. At this time, the viscosity of the ink does not exceed 30cps. This low viscosity can ensure that the ink is smoothly sprayed from the nozzle, ensuring smooth spraying, thereby ensuring the printing quality; moreover, after the ink is sprayed from the nozzle, the temperature drops rapidly and the viscosity increases rapidly. The viscosity at room temperature is 100-120cps. This high viscosity can meet the printing requirements, not only can it bring better electrical, mechanical and weather resistance properties to the cured film, but more importantly, it can form a better coating structure at the edges and corners of the substrate, thereby effectively preventing the ink from sagging at these locations and destroying the insulation properties after film formation;
[0043] 2) The UV curable inkjet printing power battery blue film ink with high viscosity (100-120 cps) at room temperature (25°C) provided by the present invention is prepared by screening an acrylate resin with suitable viscosity, adjusting the mass ratio of the acrylate resin to the UV photocurable monomer to 1: (1.5-3), and adjusting the mass ratio of the monofunctional photocurable monomer to the difunctional photocurable monomer in the UV photocurable monomer to (0.3-1.5): 1. For example, the addition of tripropylene glycol diacrylate (TPGDA) and dipropylene glycol diacrylate (DPGDA) can increase the curing speed of the coating, increase the flexibility of the coating, and increase the dilution power of the ink on the color paste, while the viscosity of the system can be further adjusted by tricyclodecane dimethanol diacrylate (DCPDA) to meet the use requirements; in addition, DCPDA can also improve the weather resistance of the coating, making it less prone to aging and discoloration in harsh environments such as sunlight, high temperature, and humidity, and maintaining the stable appearance and performance of the ink after printing.
[0044] 3) The UV curable inkjet printing power battery blue film ink provided by the present invention is used in combination with a hydrophobic monomer and a UV photocurable monomer, and the hydrophobic modification increases the degree of crosslinking between molecules, and the molecular network structure is more easily formed, increasing the degree of crosslinking between polymer molecules, thereby improving the flexibility and curing speed of the coating. Moreover, after the obtained blue film ink is soaked in 85°C hot water for 30 days, there is no obvious change in the coating, and there is no breakdown point in the withstand voltage test; after 1000h of aging resistance to double 85, there is no obvious change in the coating, meeting the adhesion level 0, and the dielectric strength is maintained at 54kV / mm; the results of electrolyte immersion resistance, acid and alkali immersion resistance for 72h, and salt spray resistance for 720h are all passed, so the UV curable inkjet printing power battery blue film ink provided by the present invention is more outstanding in weather resistance than the traditional battery blue film ink.
[0045] 4) The UV-curable inkjet printing power battery blue film ink provided by the present invention is combined with DCPDA and acrylic resin, and the addition ratio of surfactant and free radical polymerization inhibitor is adjusted at the same time, thereby improving the thermal stability of the color paste in the ink, which is conducive to high-viscosity printing.
[0046] In summary, the UV curable inkjet printing power battery blue film ink provided by the present invention has a high viscosity (100-120cps) at room temperature (25°C), and the ink material is sprayed under relatively high temperature (60-95°C) conditions. At this time, the viscosity of the ink does not exceed 30cps. This low viscosity can ensure that the ink is ejected smoothly from the nozzle, ensuring smooth jetting, thereby ensuring the printing quality. In other words, the UV curable inkjet printing power battery blue film ink provided by the present invention can maintain high viscosity at room temperature to meet the inkjet printing requirements, and can require a lower viscosity when the nozzle is sprayed to ensure smooth jetting, has excellent insulation and protection functions, and can meet the protection requirements of new energy vehicle batteries for no less than 15 years. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 These are the adhesion test results of the UV-cured coatings obtained in Examples 1 and 2 of the present invention after aging;
[0048] Figure 2 These are the impact resistance test results of the UV-cured coatings obtained in Examples 1 to 5 of the present invention;
[0049] Figure 3 This is the impact resistance test result of the UV-cured coating obtained in Example 2;
[0050] Figure 4 is an optical microscope (OM) image of the R angle of the printed hemming of Example 1;
[0051] Figure 5 This is an optical microscope (OM) image of the R angle of the printed edge of Comparative Example 1. DETAILED DESCRIPTION
[0052] Here, exemplary embodiments will be described in detail, and the embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are only examples consistent with some aspects of the present invention described in detail in the appended claims.
[0053] The preparation method of the UV curing coating disclosed in the present invention has the following specific preparation process:
[0054] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with embodiments.
[0055] Example 1
[0056] This embodiment provides a UV curable inkjet printing power battery blue film ink, including the following components in parts by weight:
[0057] 55 parts of an acrylic resin, comprising: 30 parts of isobornyl acrylate (IBOA), 25 parts of polyurethane acrylate (5 parts of polyurethane acrylate R7162, 20 parts of polyurethane acrylate 33118);
[0058] 32 parts of UV photocurable monomers, including: 15 parts of tripropylene glycol diacrylate (TPGDA), 2 parts of 1,6-hexanediol diacrylate (HDDA) and 15 parts of tricyclodecane dimethanol diacrylate (DCPDA);
[0059] 3 parts of a hydrophobic monomer, which includes: 1 part of lauryl acrylate (LA) and 2 parts of tetradecyl acrylate (TDA);
[0060] 0.5 parts of an auxiliary agent, which includes: 0.3 parts of BYK3575 and 0.2 parts of a free radical polymerization inhibitor (2,6-di-tert-butyl-p-cresol);
[0061] 4.5 parts of photoinitiator, including: 0.6 parts of photoinitiator 784, 0.8 parts of photoinitiator 184, 0.5 parts of photoinitiator BP, 1.6 parts of photoinitiator 819, and 1 part of photoinitiator ITX;
[0062] 4 parts of color paste.
[0063] Specifically, the preparation method of the above-mentioned UV curable inkjet printing power battery blue film ink is as follows:
[0064] (1) In a yellow light production workshop, add acrylic resin and UV photocurable monomer into a dispersion tank according to the formula weight, start the disperser, and stir until uniform and clear;
[0065] (2) Continue to add additives and initiators to the dispersion tank according to the formula weight, and continue stirring until the initiator is completely dissolved and the liquid is uniform and transparent;
[0066] (3) Add color paste and continue stirring for 30 minutes;
[0067] (4) In a Huangguang dust-free workshop, the power battery blue film ink (I) is filtered through 1 μm, 0.45 μm and 0.22 μm filter elements in sequence, and the power battery blue film ink (I) is placed in a black plastic barrel, and after the viscosity and particle size are tested and qualified, it is sealed and stored away from light.
[0068] Furthermore, the specific process of forming a cured coating using the above-mentioned power battery blue film ink (I) is as follows:
[0069] Step 1: The power battery blue film ink is attached to the surface of the power battery shell by inkjet printing. The specific printing nozzle can be XAAR nozzle;
[0070] Step 2: pre-curing the surface after inkjet printing in step 1 by using a UV-LED lamp, and then inkjet printing again on the pre-cured surface, repeating the above pre-curing step twice, and finally inkjet printing again on the pre-cured surface, and then using a UV-LED lamp for UV curing;
[0071] Step 3: Use an electrodeless lamp to perform electrodeless lamp curing on the surface after UV curing in step 2, and finally form a cured coating (I) with a dry film thickness of 100 μm.
[0072] Example 2
[0073] This embodiment provides a UV curable inkjet printing power battery blue film ink, including the following components in parts by weight:
[0074] 55 parts of an acrylic resin, wherein the acrylic resin is 30 parts of isobornyl acrylate (IBOA) and 25 parts of acrylated polyacrylate 4312IH;
[0075] 32 parts of UV photocurable monomers, including: 22 parts of dipropylene glycol diacrylate (DPGDA), 2 parts of 1,6-hexanediol diacrylate (HDDA) and 8 parts of tricyclodecane dimethanol diacrylate (DCPDA);
[0076] 5 parts of a hydrophobic monomer, which includes: 3 parts of lauryl acrylate (LA) and 2 parts of hexadecyl acrylate (HDA);
[0077] 0.5 parts of an auxiliary agent, which includes: 0.2 parts of BYK3575 and 0.3 parts of a free radical polymerization inhibitor (N-nitroso-N-phenylhydroxylamine aluminum);
[0078] 4.5 parts of photoinitiator, including: 0.6 parts of photoinitiator 784, 0.8 parts of photoinitiator 184, 0.5 parts of photoinitiator BP, 1.6 parts of photoinitiator 819, and 1 part of photoinitiator ITX;
[0079] 3 parts of color paste.
[0080] Furthermore, the same method for preparing UV-curable inkjet printing power battery blue film ink as in Example 1 was adopted to prepare power battery blue film ink (II), and the power battery blue film ink (II) was put into a black plastic barrel, and after the viscosity and particle size were tested and qualified, the barrel was sealed and stored away from light.
[0081] The above-mentioned power battery blue film ink (II) was used to print a UV-curable coating (II) with a dry film thickness of 100 μm using the technology of two UV-LED pre-curing, one UV-LED curing, and one electrodeless lamp curing.
[0082] Example 3
[0083] This embodiment provides a UV curable inkjet printing power battery blue film ink, including the following components in parts by weight:
[0084] 58 parts of an acrylic resin, wherein the acrylic resin is 25 parts of isobornyl acrylate (IBOA), 8 parts of polyurethane acrylate R7162, and 25 parts of polyurethane acrylate DR-U021;
[0085] 28 parts of UV photocurable monomers, comprising: 18 parts of tripropylene glycol diacrylate (TPGDA) and 10 parts of tricyclodecane dimethanol diacrylate (DCPDA);
[0086] 4 parts of a hydrophobic monomer, comprising: 2 parts of lauryl acrylate (LA) and 2 parts of hexadecyl acrylate (HDA);
[0087] 0.5 parts of an auxiliary agent, which includes: 0.25 parts of BYK3575 and 0.25 parts of a free radical polymerization inhibitor (N-nitroso-N-phenylhydroxylamine aluminum);
[0088] 3.5 parts of photoinitiator, including: 0.5 parts of photoinitiator 784, 0.5 parts of photoinitiator 184, 0.5 parts of photoinitiator BP, 1 part of photoinitiator 819, and 1 part of photoinitiator ITX;
[0089] 6 parts of color paste.
[0090] Furthermore, the same method for preparing UV-curable inkjet printing power battery blue film ink as in Example 1 was adopted to prepare power battery blue film ink (III), and the power battery blue film ink (III) was put into a black plastic barrel, and after the viscosity and particle size were tested and qualified, the barrel was sealed and stored away from light.
[0091] The above-mentioned power battery blue film ink (III) was used to print a UV-curable coating (III) with a dry film thickness of 100 μm using the technology of two UV-LED pre-curing, one UV-LED curing, and one electrodeless lamp curing.
[0092] Example 4
[0093] This embodiment provides a UV curable inkjet printing power battery blue film ink, including the following components in parts by weight:
[0094] 50 parts of an acrylic resin, comprising: 25 parts of isobornyl acrylate (IBOA), 25 parts of polyurethane acrylate (5 parts of polyurethane acrylate R7162, 20 parts of polyurethane acrylate B-270);
[0095] 32 parts of UV photocurable monomers, including: 24 parts of tripropylene glycol diacrylate (TPGDA), 2 parts of 1,6-hexanediol diacrylate (HDDA) and 11 parts of tricyclodecane dimethanol diacrylate (DCPDA);
[0096] 4 parts of a hydrophobic monomer, which includes: 2 parts of lauryl acrylate (LA) and 2 parts of tetradecyl acrylate (TDA);
[0097] 0.6 parts of an auxiliary agent, which includes: 0.4 parts of BYK3575 and 0.2 parts of a free radical polymerization inhibitor (2,6-di-tert-butyl-p-cresol);
[0098] 4.4 parts of photoinitiator, including: 0.8 parts of photoinitiator 784, 0.8 parts of photoinitiator 184, 0.8 parts of photoinitiator BP, 1 part of photoinitiator 819, and 1 part of photoinitiator ITX;
[0099] 4 parts of color paste.
[0100] Furthermore, the same method for preparing UV-curable inkjet printing power battery blue film ink as in Example 1 was adopted to prepare power battery blue film ink (IV), and the power battery blue film ink (IV) was put into a black plastic barrel, and after the viscosity and particle size were tested and qualified, the barrel was sealed and stored away from light.
[0101] The above-mentioned power battery blue film ink (IV) was used to print a UV-curable coating (IV) with a dry film thickness of 100 μm using the technology of two UV-LED pre-curing, one UV-LED curing, and one electrodeless lamp curing.
[0102] Example 5
[0103] This embodiment provides a UV curable inkjet printing power battery blue film ink, including the following components in parts by weight:
[0104] 49 parts of an acrylic resin, comprising: 20 parts of isobornyl acrylate (IBOA), 19 parts of polyurethane acrylate DR-U021, and 10 parts of acrylic acid esterified polyacrylate 4312IH;
[0105] 40 parts of UV photocurable monomers, comprising: 18 parts of dipropylene glycol diacrylate (DPGDA) and 22 parts of tricyclodecane dimethanol diacrylate (DCPDA);
[0106] 3 parts of a hydrophobic monomer, comprising: 1 part of lauryl acrylate (LA) and 2 parts of hexadecyl acrylate (HDA);
[0107] 0.5 parts of an auxiliary agent, which includes: 0.2 parts of BYK3575 and 0.3 parts of a free radical polymerization inhibitor (2,6-di-tert-butyl-p-cresol);
[0108] 3.5 parts of photoinitiator, including: 0.5 parts of photoinitiator 784, 0.5 parts of photoinitiator 184, 0.5 parts of photoinitiator BP, 1 part of photoinitiator 819, and 1 part of photoinitiator ITX;
[0109] 4 parts of color paste.
[0110] Furthermore, the same method for preparing UV-curable inkjet printing power battery blue film ink as in Example 1 was adopted to prepare power battery blue film ink (V), and the power battery blue film ink (V) was put into a black plastic barrel, and after the viscosity and particle size were tested and qualified, the barrel was sealed and stored away from light.
[0111] The above-mentioned power battery blue film ink (V) was used to print a UV-curable coating (V) with a dry film thickness of 100 μm using the technology of two UV-LED pre-curing, one UV-LED curing, and one electrodeless lamp curing.
[0112] Comparative Example 1
[0113] This comparative example provides a UV curable inkjet printing power battery blue film ink (VI), comprising the following components in parts by weight:
[0114] 48 parts of an acrylic resin, wherein the acrylic resin is 20 parts of isobornyl acrylate (IBOA) and 28 parts of polyurethane acrylate B-270;
[0115] 38 parts of UV photocurable monomers, including: 16 parts of tripropylene glycol diacrylate (TPGDA) and 22 parts of 1,6-hexanediol diacrylate (HDDA);
[0116] 2 parts of a hydrophobic monomer, comprising: 1 part of lauryl acrylate (LA) and 1 part of hexadecyl acrylate (HDA);
[0117] 0.4 parts of additive BYK3575;
[0118] 3.6 parts of photoinitiator, including: 0.6 parts of photoinitiator 784, 1 part of photoinitiator 184, 0.5 parts of photoinitiator BP, 1 part of photoinitiator 819, and 0.5 parts of photoinitiator ITX;
[0119] 8 parts of color paste.
[0120] Furthermore, the same method for preparing UV-curable inkjet printing power battery blue film ink as in Example 1 was adopted to prepare power battery blue film ink (six), and the power battery blue film ink (six) was put into a black plastic barrel, and after the viscosity and particle size were tested and qualified, the barrel was sealed and stored away from light.
[0121] The above-mentioned power battery blue film ink (six) was used to print a UV-curable coating (six) with a dry film thickness of 100 μm using the technology of two UV-LED pre-curing, one UV-LED curing, and one electrodeless lamp curing.
[0122] Comparative Example 2
[0123] This comparative example provides a UV curable inkjet printing power battery blue film ink (VII), comprising the following components in parts by weight:
[0124] 45 parts of an acrylic resin, wherein the acrylic resin is 30 parts of isobornyl acrylate (IBOA) and 15 parts of polyurethane acrylate 33118;
[0125] 45 parts of UV photocurable monomers, comprising: 30 parts of dipropylene glycol diacrylate (DPGDA) and 15 parts of tricyclodecane dimethanol diacrylate (DCPDA);
[0126] 3 parts of a hydrophobic monomer, which includes: 2 parts of lauryl acrylate (LA) and 1 part of tetradecyl acrylate (TDA);
[0127] 0.4 parts of additives, including 0.2 parts of BYK333 and 0.2 parts of free radical polymerization inhibitor (2,6-di-tert-butyl-p-cresol);
[0128] 2.6 parts of photoinitiator, including: 0.5 parts of photoinitiator 784, 0.5 parts of photoinitiator 184, 0.5 parts of photoinitiator BP, 1 part of photoinitiator 819, and 0.1 parts of photoinitiator ITX;
[0129] 4 parts of color paste.
[0130] Furthermore, the same method for preparing UV-curable inkjet printing power battery blue film ink as in Example 1 was adopted to prepare power battery blue film ink (VII), and the power battery blue film ink (VII) was put into a black plastic barrel, and after the viscosity and particle size were tested and qualified, the barrel was sealed and stored away from light.
[0131] The above-mentioned power battery blue film ink (VII) was used to print a UV-curable coating (VII) with a dry film thickness of 100 μm using the technology of two UV-LED pre-curing, one UV-LED curing, and one electrodeless lamp curing.
[0132] Comparative Example 3
[0133] This comparative example provides a UV curable inkjet printing power battery blue film ink (VIII), comprising the following components in parts by weight:
[0134] 69 parts of an acrylic resin, wherein the acrylic resin is 30 parts of isobornyl acrylate (IBOA), 9 parts of polyurethane acrylate R7162 and 30 parts of polyurethane acrylate 33118;
[0135] 17 parts of UV photocurable monomers, including: 15 parts of tripropylene glycol diacrylate (TPGDA) and 2 parts of 1,6-hexanediol diacrylate (HDDA);
[0136] 5 parts of a hydrophobic monomer, which includes: 3 parts of lauryl acrylate (LA) and 2 parts of tetradecyl acrylate (TDA);
[0137] 0.5 parts of additives, including 0.3 parts of BYK3575 and 0.2 parts of free radical polymerization inhibitor (2,6-di-tert-butyl-p-cresol);
[0138] 4.5 parts of photoinitiator, including: 0.6 parts of photoinitiator 784, 0.8 parts of photoinitiator 184, 0.5 parts of photoinitiator BP, 1.6 parts of photoinitiator 819, and 1 part of photoinitiator ITX;
[0139] 4 parts of color paste.
[0140] Furthermore, the same method for preparing UV-curable inkjet printing power battery blue film ink as in Example 1 was adopted to prepare power battery blue film ink (eight), and the power battery blue film ink (eight) was put into a black plastic barrel, and after the viscosity and particle size were tested and qualified, the barrel was sealed and stored away from light.
[0141] The above-mentioned power battery blue film ink (eight) was used to print a UV-curable coating (eight) with a dry film thickness of 100 μm using the technology of two UV-LED pre-curing, one UV-LED curing, and one electrodeless lamp curing.
[0142] In order to further verify the effectiveness and feasibility of the technical solution provided by the present invention, the inventors used the UV curing coating preparation method of the present invention to prepare a curing coating with a dry film thickness of 100 μm for the power battery blue film ink of the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 3 and performed performance tests, as follows:
[0143] (1) Thermal stability test: The ink slurry was aged at 100°C for 240 hours and its discoloration, shedding, and wrinkling were observed.
[0144] (2) 100-grid adhesion test standard: GB / T 9286-1998
[0145] (3) Impact resistance test standard: GB / T 1732-2020
[0146] (4) Wear resistance test standard: GB / T 1768-2006
[0147] (5) Insulation resistance test method: Safety tester DC 1000V, 60s
[0148] (6) Dielectric strength test standard: ASTM D 149-97a
[0149] (7) Double 85 test conditions: temperature 85°C, relative humidity 85%
[0150] (8) Cylindrical diameter 32mm bending test standard: GB / T 6742-2007
[0151] (9) Curing speed: It is measured by whether the ink is completely dry after the film layer with the same film thickness passes through a fixed light product. If it is dry, it passes; otherwise, it fails. The light product E = ∫P(t)dt, where P(t) is the power of light and t is the time. The light product of the curing stage is shown in Table 1:
[0152] Table 1
[0153] <![CDATA[Light integral amount (mJ·cm -2 )]]> UV-LED pre-curing 2433 UV-LED Curing 3757 Electrodeless lamp curing 5712
[0154] After testing, the performance results of the UV-cured coatings in various embodiments and comparative examples are shown in Table 2 below:
[0155] Table 2
[0156]
[0157]
[0158] Regarding the chemical resistance test, the specific test steps are as follows:
[0159] (1) 85℃ hot water resistance test standard: GB / T 1733-1993 Method A, set temperature 85℃
[0160] (2) Acid, alkali and electrolyte resistance test standard: GB / T 9274-1988
[0161] (3) Salt spray resistance test standard: GB / T 1771-2007
[0162] After testing, the chemical resistance test results of the UV-cured coatings in various embodiments and comparative examples are shown in Table 3 below:
[0163] Table 3
[0164] Resistant to 85℃ hot water for 1000h Resistant to electrolyte immersion for 72h Acid and alkali resistant soaking for 72h Salt spray resistance test 720h Example 1 pass pass pass pass Example 2 pass pass pass pass Example 3 pass pass pass pass Example 4 pass pass pass pass Example 5 pass pass pass pass Comparison 1 2h foaming 24h blistering and shedding pass 96h blistering and shedding Comparison 2 48h foaming pass 24h blistering and shedding 120h cracking and falling off Contrast 3 48h foaming pass 24h blistering and shedding 100h cracking and falling off
[0165] Test result analysis:
[0166] It can be seen from the results of Examples 1 to 5 and Comparative Examples 1 to 3 that the specific component ratio of the present invention has the characteristics of heat resistance and water boiling resistance, and realizes the characteristics of low viscosity (as low as 22.3mPa·s) when the nozzle is sprayed in a high temperature environment (60 to 95°C), which meets the nozzle spraying requirements, and has high viscosity at room temperature, which can meet the requirements of uniform edge wrapping of the battery shell during printing, while ensuring the curing speed, flexibility and weather resistance of the ink. After the obtained blue film ink was soaked in 85°C hot water for 30 days, there was no obvious change in the coating, and there was no breakdown point in the pressure test; after 1000h of double 85 aging, there was no obvious change in the coating, meeting the adhesion level 0, such as Figure 1As shown. The dielectric strength is maintained at about 54kV / mm. The electrolyte immersion resistance, acid and alkali immersion resistance for 72h, and salt spray resistance for 720h have all passed the test. The DC1000V insulation resistance is about 190GΩ, and the insulation performance is better than the comparative example (about 170GΩ). In addition, after being stored in a 100℃ constant temperature box for 240h, the ink is not solidified, the color paste in the ink has not settled and stratified, the viscosity changes <2%, and the particle size (dynamic light scattering test) changes <5%, which has excellent high temperature storage performance.
[0167] Figure 2 The results of the impact resistance test after the inks in Examples 1 to 5 are cured and formed into films. The results show that all the examples have passed the impact resistance test and met the test requirements. Figure 3 It can be seen that in Comparative Example 2, there is an obvious fracture layer (marked ×), and it fails to pass the impact resistance test, indicating that its flexibility is insufficient.
[0168] In contrast, no inhibitor is added to comparative example 1, and the mass ratio of UV photocurable monomer to acrylate resin in comparative example 2 is 1:1, which is less than the minimum mass ratio of 1.5 required by the present invention. In comparative example 3, no DCPDA is added, and the mass ratio of monofunctional photocurable monomer to bifunctional photocurable monomer is greater than 1.5, and the mass ratio of UV photocurable monomer to acrylate resin is less than 1.5. The results all show that there are cracks and sedimentation in the impact resistance test, and the viscosity of the ink exceeds 30cps, which affects the smooth ejection of the ink. The double 85 test also shows different degrees of shedding and cracking, and weather resistance (resistance to 85℃ hot water for 1000h, resistance to electrolyte immersion for 72h, resistance to acid and alkali immersion for 72h, and resistance to salt spray test for 720h) also shows different degrees of bubbling or shedding. It can be seen that the proportion of each type of monomer will affect the flexibility and resistance of the final ink.
[0169] Figure 4 This is an optical microscope (OM) image of the printed edge R angle of Example 1. Figure 5 This is the optical microscope (OM) image of the R angle of the printed edge of comparative example 1. The solidified thickness at the plane of the battery shell is 100-120 μm. If there is no obvious boundary line at the printed edge and the minimum solidified thickness at the R angle is greater than 70 μm, the edge at the R angle is considered qualified, otherwise it is not passed. The R angle refers to the corner between the two planes of the battery shell. Figure 4 The results show that there is no obvious boundary line at the printed edge of the embodiment and the minimum cured thickness at the R corner is 90.2 μm, which is a qualified product. Figure 5 There is no obvious boundary line at the printed edge of the comparative example and the minimum curing thickness at the R corner is 55.2μm, so the product is unqualified.
[0170] In summary, the various components in the UV-curing inkjet printing power battery blue film ink cooperate with each other and work together to make the ink have excellent technical effects such as fast curing speed, good flexibility, strong weather resistance and stable viscosity, which can meet the needs of power battery blue film printing.
[0171] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.
[0172] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A UV curable inkjet printing power battery blue film ink, characterized in that: The invention comprises the following components in parts by weight: 25 to 80 parts of acrylic resin, 15 to 40 parts of UV photocurable monomer, 2 to 10 parts of hydrophobic monomer, 0.1 to 1 part of auxiliary agent, 2 to 8 parts of photoinitiator and 2 to 7 parts of color paste; the mass ratio of the acrylic resin to the UV photocurable monomer is 1:(1.5 to 3).
2. According to claim 1, the UV curable inkjet printing power battery blue film ink is characterized in that: The acrylic resin is one of polyurethane acrylate and acrylated polyacrylate, or a mixture of the two.
3. According to claim 2, the UV curable inkjet printing power battery blue film ink is characterized in that: The viscosity of the polyurethane acrylate is 10-8000 cps at 25° C., and the viscosity is 600-5000 cps at 60° C.
4. The UV curable inkjet printing power battery blue film ink according to claim 2, characterized in that: The acrylic acid esterified polyacrylate has a viscosity of 3000-40000 cps at 25°C and a glass transition temperature of 50°C-100°C.
5. The UV curable inkjet printing power battery blue film ink according to claim 1, characterized in that: The UV photocurable monomer is a mixture of a monofunctional UV photocurable monomer and a difunctional UV photocurable monomer, and the mass ratio of the monofunctional UV photocurable monomer to the difunctional UV photocurable monomer is (0.3-1.5):
1.
6. The UV curable inkjet printing power battery blue film ink according to claim 5, characterized in that: The monofunctional UV photocurable monomer is an aliphatic or alicyclic (meth) acrylic photocurable monomer.
7. The UV curable inkjet printing power battery blue film ink according to claim 1, characterized in that: The hydrophobic monomer is an acrylic acid ester hydrophobic monomer with an ester carbon chain length of C8 to C18.
8. The UV curable inkjet printing power battery blue film ink according to claim 1, characterized in that: The viscosity of the UV curable inkjet printing power battery blue film ink at 60° C. does not exceed 30 cps, and the viscosity at room temperature is 100-120 cps.
9. A UV curing coating, characterized in that: The method is formed by inkjet printing the UV curable inkjet printable power battery blue film ink as described in any one of claims 1 to 8.
10. The UV curing coating according to claim 9, characterized in that: The thickness of the UV curing coating is 100-120 μm.
Citation Information
Patent Citations
UV curing ink-jet printing insulating ink and UV curing coating
CN116445036A
Cited By
Preparation method and application of micronized stable UV insulating jet ink
CN120272055A
Preparation method and application of a micro-particleized stable uv insulating inkjet
CN120272055B
Photocuring printing ink for insulation protection of lithium battery component and preparation method of photocuring printing ink
CN121610116A
Radiation curable ink compositions, and articles and assemblies therefrom
WO2026170448A1